2009
DOI: 10.1063/1.3223326
|View full text |Cite
|
Sign up to set email alerts
|

Silica structural changes induced by thermal treatment or ionic implantation as probed by IR reflectance spectroscopy

Abstract: Fourier transformed infrared microreflectance spectroscopy is used to probe and compare the consequences of thermal quenching or ionic implantation on the structure of silica. A linear change in the main structural feature associated with Si–O–Si vibration with fictive temperature (Tf) is observed up to Tf=1400 °C. Ionic implantation is shown to shift the frequency of the main IR Si–O–Si vibration toward much lower wavenumbers, for all deposited energies, indicating that a comparison can be drawn between ficti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…For Bibent's annealing times, 7 they look also consistent with our measurements apart from the 1200°C value, which appears underestimated.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For Bibent's annealing times, 7 they look also consistent with our measurements apart from the 1200°C value, which appears underestimated.…”
Section: Discussionsupporting
confidence: 89%
“…The equilibrium time needed for 1000°C for instance is about 20 days, which looks unrealistic with the needed stability of the whole Raman spectroscopy setup. Moreover, the evolution upon annealing at 1000°C is expected to be very small, as the starting T F is about 1020°C (see in Section II (1) ). The annealing times chosen by Ryu and Tomozawa 8 look to be well consistent with our relaxation time data. For Bibent's annealing times, 7 they look also consistent with our measurements apart from the 1200°C value, which appears underestimated. The relaxation times measured by Tomozawa et al 9 at 1050° and 1100°C appear somewhat lower than the present ones, by about one order of magnitude. The annealing times applied by Goller et al 10 are much lower than the relaxation times found in this paper.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Several studies have recently been initiated to refine the underlying analogy between the structural state created by a displacement cascade and major thermal quenching (Bureau, 2008, Bibent et al, 2009, Peuget et al, 2013. The thermal history of the glass at the core of a displacement cascade was determined by molecular dynamics calculations (Bureau, 2008).…”
Section: Origin Of the Evolution Of The Glass Structurementioning
confidence: 99%
“…Many of the works concerning ion irradiations in silica are related to the changes induced by irradiation, namely densification effects [2], modifications in optical properties (refractive index [3], ionoluminescence [4,5], optical [6,7,8,9] and infrared [7,10,11,12,13] absorption and reflectance [14], Raman scattering [10,15,16]), mechanical properties (near-surface hardness [16,17], compaction and plastic flow [18]), chemical stability [19] and etching rate of the irradiated surfaces [1,3,6]. From these works it is concluded that microscopic and macroscopic structural modifications can both saturate at some lattice damage level depending on the density of deposited energy [3].…”
Section: Introductionmentioning
confidence: 99%